2022
DOI: 10.1007/s00404-022-06413-7
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic risk assessment for an unplanned operative delivery: a prospective study

Abstract: Purpose: To assess the value of pre-labor maternal and fetal sonographic variables to predict an unplanned operative delivery.Methods: In this prospective study, nulliparous women were recruited at 37.0-42.0 weeks of gestation.Sonographic measurements included estimated fetal weight, maternal pubic arch angle, and the angle of progression. We performed a descriptive and comparative analysis between two outcome groups: spontaneous vaginal delivery (SVD) and unplanned operative delivery (UOD) (vacuum-assisted, f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Logistic regression analysis revealed that the SPAA was significantly associated with vaginal delivery. Moreover, the sensitivity of SPAA in this event was significant (AUC, 0.782; P = 0.000; 95%CI: 0.717–0.848), a finding consistent with a study by Perlman et al [ 11 ]. However, this result conflicted with data from the study by Albrich et al [ 7 ] in 2015, who failed to find an association between the SPAA and vaginal delivery.…”
Section: Discussionsupporting
confidence: 91%
“…Logistic regression analysis revealed that the SPAA was significantly associated with vaginal delivery. Moreover, the sensitivity of SPAA in this event was significant (AUC, 0.782; P = 0.000; 95%CI: 0.717–0.848), a finding consistent with a study by Perlman et al [ 11 ]. However, this result conflicted with data from the study by Albrich et al [ 7 ] in 2015, who failed to find an association between the SPAA and vaginal delivery.…”
Section: Discussionsupporting
confidence: 91%